Modernisasi Pendidikan Islam Menurut Azyumardi Azra: Diskursus Modernisasi di Pondok Pesantren Al-Aqobah Jombang - Muhammad Alfan Nur Rois (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
Islamic boarding schools are considered as backward and less participatory traditional institutions, but have great potential in terms of mobilizing local resources, potential sources of labor, and sources of political support. With the development of increasingly advanced times, Islamic boarding schools need to modernize holistically institutionally, curriculum and learning methods. For this reason, the author tries to reveal the modernization of Islamic education according to Azyumardi Azra at the Al-Aqobah Islamic boarding school, Jombang. The results of this study found that the institutional modernization of the Islamic education system at the al-Aqobah Islamic boarding school still adheres to the classic pesantren tradition while at the same time innovating with modernity. Thus making the Al-Aqobah Islamic boarding school transform into a hybrid, namely combining salaf (traditional) and khalaf (modern). Modernization of the curriculum at the Al-Aqobah Islamic boarding school has at least fulfilled religious education (tafaqquh fi al-din), madrasah, formal schools, and skills education. Meanwhile, the modernization of learning methods has also used a variety of up-to-date technological devices to support learning objectives and the use of contemporary teaching materials and learning media.